BE_VERWALTUNGSGERICHT 100 2017 196 vom 19. März 2018 - BE Verwaltungsgericht (2018)
Strassenplan \x3C\x3CUmgestaltung Oberlandstrasse, Spiez\x3E\x3E (RRB 511/2017 vom 31. Mai 2017 - 32.08-15.13) | Nutzungspläne